A gestão do conhecimento na área de gestão de pessoas da Universidade Federal da Paraíba - Diniz, Ana Clécia de Medeiros (2014)
The research discusses how to exercise the knowledge management in the context of the Dean of Personnel Management (Progep) a federal institution of higher education, the Federal University of Paraíba (UFPB). The strategy of exploratory research was quantitative, with descriptive and analytical approach, based on a case study from the method Organizational Knowledge Assessment (OKA), developed by the World Bank. Performs the diagnosis of knowledge management, discussing their concepts, identifying aspects, and existing processes, measuring up the maturity stage, interpreting the existing metrics, and considering the dimensions "People", "Processes" and "Systems" . The research involved four phases: document analysis, interviews with leaders, application of OKA method and analysis of results. Applied a questionnaire containing 199 questions with metrics for analyzing 14 dimensions. The sample field consist of 24 managers, of which thirteen answered the questionnaire in mixed form. The results were summarized and interpreted; and presented by the radar diagram type, with the overall vision of the organization (mean score obtained with the responses of all subjects) and associated with each dimension score. In 43% of the analyzed dimensions was evident a conceptual alignment between senior managers (AG) and middle managers (GI). The dimensions belonging to the People element achieved the highest score (20.02) on the radar of GI, which is considered in the context of OKA median, and average on the radar of the two groups the score was high (22.38); while those dimensions on the elements Processes and systems had lower yield management practices knowledge to obtain median score on scale processes (16.7) for GI and high (21.56) for the AG. And regarding those systems had a median score (16.2) for GI, high (23.07) for the AG and median (19.65) for the average of both - with the exception of high scores in the People element (24 , 72) and processes (26,44) demonstrated the radar generated by the AG. It is recorded also that the lack of an institutional program of knowledge management deficitariamente impacted the dimensions analyzed by the OKA. The completion of the Diagnostic and a qualitative analysis of indicators obtained in the study indicate Pará as dimensions that need to be worked in Progep / UFPB , para and a need to recognize what the unit has a key role in creation process and management of institutional knowledge , proposing actions for improvement of these dimensions and para new study points possible futures.